Main concepts of Valued Added Tax - Villanueva Gutiérrez, Walker (2021)
The main purpose of this article is to present the most relevant aspects of the Value Added Tax (VAT) in Peru. For that purpose, the aim of taxes is explained, as well as a brief description of indirect taxes. Likewise, the principle of neutrality is recognized as a neuralgic concept to understand the VAT. Based on this, an approximation is made from the economic foundations of the tax, such as value added and consumption, to finally, and under this premise, analyze its legal regulation, which uses concepts of Private Law.